Prognostic Value of Preoperative Peak Expiratory Flow to Predict Postoperative Pulmonary Complications in Surgical Lung Cancer Patients - Chang, Shuai; Zhou, Kun; Wang, Yan; Lai, Yutian; Che, Guowei (Frontiers in Oncology, 2021)
Objectives: Cough impairment may lead to excessive accumulation of pulmonary secretions and increase the risk of postoperative pulmonary complications (PPCs). Peak expiratory flow (PEF) is a sensitive indicator of cough ability. We aimed to investigate the correlation between PEF and PPCs for lung cancer patients undergoing lobectomy or segmental resection for improved risk assessment. Methods: This retrospective study assessed 560 patients with non-small cell lung cancer admitted for surgery between January 2014 to June 2016. The measurements of PEF were performed before surgery and the clinical outcomes were recorded, including PPCs, postoperative hospital stay, hospitalization costs, and other variables. Results: Preoperative PEF was significantly lower in PPCs group compared to non-PPCs group (294.2 ± 95.7 vs. 363.0 ± 105.6 L/min, P < 0.001). Multivariable regression analysis showed that high PEF (OR=0.991, 95%CI: 0.988-0.993, P<0.001) was an independent protective factor for PPCs. According to the receiver operating characteristic (ROC) curve, a PEF value of 250 L/min was selected as the optimal cutoff value in female patients, and 320 L/min in male patients. Patients with PEF under cutoff value of either sex had higher PPCs rate and unfavorable clinical outcomes. Conclusions: Preoperative PEF was found to be a significant predictor of PPCs for surgical lung cancer patients. It may be beneficial to consider the cutoff value of PEF in perioperative risk assessment.